2012
DOI: 10.1016/j.rbmo.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Simple vitrification for small numbers of human spermatozoa

Abstract: Conventional freezing procedures and containers are not appropriate for spermatozoa from the testis because of their low number and poor in-situ motility, and various types of container have been utilized to freeze small numbers of spermatozoa. This study tried to develop a vitrification method for small numbers of spermatozoa using the Cell Sleeper, which is a closed type of cell-cryopreservation container. The container with spermatozoa were cooled in liquid nitrogen vapour and then stored in a cryotank. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…Biological carriers include empty zona and Volovox globator algae. Nonbiological carriers include straws, mini straws, copper loop cryoloop, calcium alginate beads, ICSI pipette microdroplets, agarose gel microspheres [AbdelHafez et al 2009], and sleeper cells [Endo et al 2012]. …”
Section: Storage Methods For Small Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological carriers include empty zona and Volovox globator algae. Nonbiological carriers include straws, mini straws, copper loop cryoloop, calcium alginate beads, ICSI pipette microdroplets, agarose gel microspheres [AbdelHafez et al 2009], and sleeper cells [Endo et al 2012]. …”
Section: Storage Methods For Small Samplesmentioning
confidence: 99%
“…Recent improvements in the volume of a sample that can be vitrified in a single container have made it a good alternative to conventional freezing [Isachenko et al 2011]. The development of closed systems for vitrification using sleeper cells has decreased the risk of cross contamination [Endo et al 2012]. Thus, vitrification has the potential to become the preferred technique used for sperm cryopreservation in the near future.…”
Section: Future Of Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, Endo et al . (, ,b) reported that a small number of human spermatozoa can be successful vitrified using Cryotop. This indicated that Cryotop may be also a suitable carrier to cryopreserve human spermatozoa.…”
Section: Introductionmentioning
confidence: 97%
“…However, it is arguable whether the spermatozoa would be infected with bacteria or pathogens mediated by liquid nitrogen, which have leaked into the PDMS chip during storage in a cryotank. According to Endo [24] and Vajta [25], the risk of contamination of germ plasma during cryopreservation and cryobanking in IVF units is small and no report mentions LN2 as a probable vehicle for disease transmission in assisted reproduction treatment. Our study failed to detect the contaminants in the cryotanks, which have been managed in a clean room at 23–28°C with air conditioning for over 5 years of continuous use (data not shown).…”
Section: Discussionmentioning
confidence: 99%